Konsep Perdagangan dalam Tafsir Al-Mishbah (Paradigma Filsafat Ekonomi Qur’ani Ulama Indonesia) - Andi Zulfikar Darussalam; Ahmad Dahlan Malik; Ahmad Hudaifah (University of Darussalam Gontor, 2017)
Today, Islamic teaching appears as a alternative economic system, where religion norms (Al-Qur’an and hadits) are to be the fundamental of it. The researcher is interested in the research of Muhammad Quraish Shihab interpretation of at-tijarah (business) concept based on the Qur’an that can be found in his al-misbah interpretation book. This research is library research. The primary data source is al-misbah interpreation. The analytical technic of this research is qualitative analysis data with tematic interpreation. At-tijarah concepts have the difference subject, object, the meaning, and contect from one verse to the other but have the same of logic thinking of the correlation and mutual law in an act. It is like a business or a trading where there are profit and loss. There are three “business model” (at-tijarah). The first is from the human to the all human kind having material qualitative. The second is from Allah SWT (The God) to the human having immaterial qualitative. The third is from Allah SWT (The God) to the human and all of human kind having material and immaterial qualitative at once.